Monetary Policy and Inequality - ANDERSEN, ASGER LAU; JOHANNESEN, NIELS; JØRGENSEN, MIA; PEYDRÓ, JOSÉ‐LUIS (Journal of Finance, 2023)
ABSTRACT We analyze the distributional effects of monetary policy on income, wealth, and consumption. We use administrative household‐level data covering the entire population in Denmark over the period 1987 to 2014 and exploit a long‐standing currency peg as a source of exogenous variation in monetary policy. We find that gains from softer monetary policy in terms of income, wealth, and consumption are monotonically increasing in ex ante income. The distributional effects reflect systematic differences in exposure to the various channels of monetary policy, especially nonlabor channels (e.g., leverage and risky assets). Our estimates imply that softer monetary policy increases income inequality.